Perbenihan Sayuran di Indonesia: Kondisi Terkini dan Prospek Bisnis Benih Sayuran - Aswaldi Anwar; , Sudarsono; Satriyas Ilyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Indonesian Vegetable Seeds: Current Condition and Prospects in Business of Vegetable Seeds